The Effect of Economic Policy Uncertainty on Stock-Commodity Correlations and Its Implications on Optimal Hedging - Badshah, I; Demirer, R; Suleman, T (Elsevier BV, 2019)
Motivated by previous studies documenting significant return and volatility effects of economic policy uncertainty (EPU) on the stock market, this study examines whether EPU has an effect on the dynamic conditional correlations between stock and commodity returns. Our findings point to a positive and significant effect of EPU on stock-commodity correlations with particularly stronger effects in the case of energy and industrial metals. The EPU effect is stronger during weak economic conditions, while VIX as a proxy of market uncertainty is generally found to be insignificant. Finally, we show that the EPU effect on correlations has investment implications as well, implied by a significant effect on optimal hedge ratios in commodities in order to mitigate stock market risks. Our results underscore the importance of selective hedging strategies in which risk managers base the timing and size of their hedging programs on future price expectations, conditional on the level of policy uncertainty state and prevalent economic conditions.
Keywords: Commodity market; Policy uncertainty; Conditional correlation